The presence of the head coach during a small-sided game: effects on players´ internal load and technical performance. [La presencia del entrenador durante un juego reducido: efectos sobre la carga interna y rendimiento técnico]. - Moisés Falces-Prieto; David Casamichana; Eduardo Sáez-Sáez de Villarreal; Bernardo Requena-Sánchez; Christopher Carling; Luis Jesús Suárez-Arronez (Ramón Cantó Alcaraz, 2015)
The aim of the study was to examine whether the presence/absence of the head coach influenced soccer players´ heart rate (HR), rating of perceived exertion (RPE) and technical performance during a small-sided game (SSG). The participants in the study were 27 young male soccer players (age: 17.0 ± 1.0 years; height: 176.0 ± 5.2 cm; weight: 67.6 ± 7.9 kg; HRmax: 195.1 ± 0.7 bpm). The SSG were practiced with the presence (PHC) or absence (AHC) of the head coach. Each SSG had duration of 6 min followed by a 5 min rest period. Significant differences were observed for HRmax (PHC: 190.4 ± 10.8; AHC: 182.0 ± 11.9), HRmean (PHC: 175.3 ± 9.4; AHC: 167.0 ± 13.1), RPE (PHC: 7.6 ± 0.8; AHC: 5.8 ± 1.1) and >90% HRmax (PHC: 54.09 ± 33.14; AHC: 46.71 ± 35.61). Significant differences in 4 technical actions: % success in passing (PHC: 59.05 ± 23.11; AHC: 71.08 ± 18.69), % Unsuccessful Passes (UP) (PHC: 40.95 ± 23.11; AHC: 28.92 ± 18.69), Number of UP (PHC: 3.19 ± 1.69; AHC: 2.26 ± 1.58) and total number of control-conduction-passes (CCP) + Successful Passes (SP) (PHC: 0.81 ± 0.83, AHC: 0.52 ± 0.64). This study shows that the presence or not of the head coach during SSG significantly influences the intensity of the players and the technical/tactical actions. Resumen El objetivo del estudio fue examinar como la presencia/ausencia del entrenador, influyó sobre la frecuencia cardíaca (FC), percepción subjetiva del esfuerzo (PSE) y rendimiento técnico durante un juego reducido (JR). Participaron 27 jugadores jóvenes (edad: 17.0 ± 1.0 años; altura: 176.0 ± 5.2 cm; peso: 67.6 ± 7.9 kg; FCmax: 195.1 ± 0.7 ppm). El JR fue realizado en presencia (PE) /ausencia (AE) del entrenador. Cada JR tuvo una duración de 6 min seguida de 5 min de recuperación. Se observaron diferencias significativas en la carga interna: PE (FCmax:190.4 ± 10.8; FCmed:175.3 ± 9.4; PSE: 7.6 ± 0.8 y >90% FCmax: 54.09 ± 33.14) AE (FCmax:182.0 ± 11.9; FCmed:167.0 ± 13.1; PSE: 5.8 ± 1.1 y >90% FCmax: 46.71 ± 35.61). Diferencias significativas en acciones técnicas: % Pases correctos (PE: 59.05 ± 23.11; AE: 71.08 ± 18.69) % Pases incorrectos (PE: 40.95 ± 23.11; AE: 28.92 ± 18.69), Número de pases incorrectos (PE: 3.19 ± 1.69; AE: 2.26 ± 1.58) y número total de control-conducción-pase correcto (PE: 0.81 ± 0.83, AE: 0.52 ± 0.64). Este estudio demuestra que la presencia o no del entrenador durante un juego reducido tiene influencia significativa en la intensidad y rendimiento técnico-táctico de los jugadores.